2019
DOI: 10.1016/j.pmedr.2019.100969
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the provision of preventive care for modifiable chronic disease risk behaviours by mental health services

Abstract: People with mental illness experience increased chronic disease burden, contributed to by a greater prevalence of modifiable chronic disease risk behaviours. Policies recommend mental health services provide preventive care for such risk behaviours. Provision of such care has not previously been synthesised. This review assessed the provision of preventive care for modifiable chronic disease risk behaviours by mental health services. Four databases were searched from 2006 to 2017. Eligible studies were observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 109 publications
(253 reference statements)
1
29
1
Order By: Relevance
“…The results are also consistent with research reporting that people with a mental health condition would find it acceptable to be provided with support to change health risk behaviours from the services they access [28,49,61,[87][88][89]. Such findings highlight the need for health and community services to adhere to existing policies and increase the provision of care for these health risk behaviours to people with a mental health condition given the reported sub-optimal provision of preventive care to date [63].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results are also consistent with research reporting that people with a mental health condition would find it acceptable to be provided with support to change health risk behaviours from the services they access [28,49,61,[87][88][89]. Such findings highlight the need for health and community services to adhere to existing policies and increase the provision of care for these health risk behaviours to people with a mental health condition given the reported sub-optimal provision of preventive care to date [63].…”
Section: Discussionsupporting
confidence: 82%
“…Internationally and in Australia, guidelines and policies acknowledge the need to provide care to all health service clients who may be at risk for inadequate physical activity and/or fruit and vegetable consumption, [51][52][53] with additional guidelines and policies existing specifically for clients with a mental health condition [54,55]. Despite the existence of these guidelines and policies, the reported effectiveness of the provision of preventive care and lifestyle interventions in mental health services to improve such health risk behaviours, [56][57][58][59][60] and the reported interest of mental health service clients in receiving support to improve these behaviours, [49,61] sub-optimal care for health risk behaviours from general practitioners [62] and community and inpatient mental health services is consistently reported [63]. For instance, a recent a meta-analysis of 26 studies found sub-optimal provision of care (less than 80% of clients in receipt of care) to address inadequate nutrition generally and physical activity across all elements of care (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mental health service, psychosocial support service, community mental health), (b) the four risk behaviours (tobacco smoking, poor nutrition, physical inactivity and harmful alcohol consumption), and (c) the study type (intervention or implementation studies). Search filters will be included for mental health service types and risk behaviours that were used in other, similar systematic reviews [ 52 , 53 ]. Search terms for study type (interventions and implementation studies) will be adapted from a glossary for dissemination and implementation research [ 54 ] and similar systematic reviews [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…A systematic search of studies published between 2006 and 2016 found 19 studies reporting the prevalence of smoking cessation care provision/receipt in acute inpatient psychiatric facilities (Bailey et al 2016). The majority (79%) of studies were undertaken prior to or during 2010, with such studies consistently suggesting care provision was sub-optimal (Sarna et al 2009;Stockings et al 2015;Williams et al 2015).…”
mentioning
confidence: 99%